2022
DOI: 10.51507/j.jams.2022.15.1.37
|View full text |Cite
|
Sign up to set email alerts
|

Injection Effect of Anti-CD3 Monoclonal Antibody on Primo Vessel in Lymph Vessel of Rabbit with Lipopolysaccharide-Induced Inflammation

Abstract: Background: The primo vascular system can be viewed as a circulatory system that plays a therapeutic function in regenerating the body tissue. The anti-CD3 monoclonal antibody was used as an immunotherapeutic agent to treat the novel coronavirus infection . Objectives: In this study, we observed the effect of injecting lymph nodes with Foralumab, an anti-human CD3 epsilon therapeutic monoclonal antibody, on primo vessels. Methods: The structure and atomic stoichiometry of the antibody were determined by transm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…The results showed that the diameter of PP−PVs gradually decreased with the occurrence of bifurcation, while the diameter of PVs showed a slight change trend (Figure 4f and 4g), and the diameter of PVs was statistically 4.18 ± 1.18 μm (Figure 4i). In previous studies, the diameter of peripheral skin PVs and mesenteric PVs is 20−50 μm, 29,30 and the diameter of PVs in the central nervous system of rats is 13 μm, 31,32 but there are almost no reports on mice central nervous system PVs. In this work, we also performed high-resolution imaging of the capillary networks of the meninges and counted their diameters, resulting in a result of 3.96 ± 0.89 μm (Figure 4c).…”
Section: Resultsmentioning
confidence: 96%
“…The results showed that the diameter of PP−PVs gradually decreased with the occurrence of bifurcation, while the diameter of PVs showed a slight change trend (Figure 4f and 4g), and the diameter of PVs was statistically 4.18 ± 1.18 μm (Figure 4i). In previous studies, the diameter of peripheral skin PVs and mesenteric PVs is 20−50 μm, 29,30 and the diameter of PVs in the central nervous system of rats is 13 μm, 31,32 but there are almost no reports on mice central nervous system PVs. In this work, we also performed high-resolution imaging of the capillary networks of the meninges and counted their diameters, resulting in a result of 3.96 ± 0.89 μm (Figure 4c).…”
Section: Resultsmentioning
confidence: 96%
“…Administration of LPS into rabbit LVs or lymph nodes to examine the role of ILVPVs and ILVPNs in response to inflammation is becoming a popular model 15,36,[41][42][43] . Lee et al using rabbits, combined LPS stimulation to enhance the size of ILVPVs for easier visualization with the fluorescent dye diaminobenzidine (DAB), which under fluorescent microscopy, using green and red filters, allows the tracking of the vessels for the construction of a PVS connectome map 15 .…”
Section: Ilvpv and Ilvpn Physiological Functionmentioning
confidence: 99%
“…Monitoring the expression of these genes can be useful in understanding the functional role of ILVPVs in pathophysiological studies. The latest rabbit study that used LPS injections into peritoneal lymph nodes reported that when administered in combination with the COVID-19 immunotherapeutic antibody Foralumab ILVPVs were further enlarged than when LPS was used alone 43 . The goal of the study was not clear; however, the authors indicate that in the presence of inflammation the antibody-induced immune response elicited greater structural changes, and thus, ILVPVs may play a central role in modulating immune responses.…”
Section: Ilvpv and Ilvpn Physiological Functionmentioning
confidence: 99%